Relative effectiveness of influenza vaccines in elderly persons in the United States, 2012/2013-2017/2018 seasons - Marina Amaral de Avila Machado (Nature Portfolio, 2021)
Abstract Influenza immunization protects seniors against influenza and its potentially serious complications. It is uncertain whether standard-dose (SD) quadrivalent vaccine offers better protection over other formulations in the elderly. In this study, we compared the effectiveness of SD-trivalent, high-dose (HD) trivalent, SD-quadrivalent, and adjuvanted trivalent vaccines in seniors (≥65 years) in a real-world setting. We selected over 200,000 individuals in each of 6 influenza seasons from 2012 to 2018 using MarketScan® databases. The two outcomes were hospitalization or emergency room (ER) visit due to (1) influenza or (2) pneumonia. Here, SD-quadrivalent was associated with higher risk of influenza-related hospitalization/ER visit (adjusted hazard ratio (aHR) 1.14 and 95% confidence interval (95% CI) 1.05–1.24) and of pneumonia-related hospitalization/ER visit (aHR 1.04 and 95% CI 1.01–1.07) vs. HD-trivalent. SD-trivalent followed similar trends compared to HD-trivalent (aHR 1.16 and 95% CI 1.06–1.27 for hospitalized/ER visit influenza; aHR 1.07 and 95% CI 1.05–1.10 for hospitalized/ER visit pneumonia). We could not demonstrate risk differences between SD vaccine formulations and between adjuvanted trivalent and one of the other three vaccines. Risk estimates slightly varied across seasons. These findings suggest that SD vaccine formulations vs. HD-trivalent were associated with higher risk of hospitalization/ER visit for influenza and pneumonia in seniors.